Pengaruh Pemutaran Film “Waspada Banjir Bandang” Terhadap Mitigasi Bencana Banjir Bandang (The Influence of Film Playback “Flash Flood Wary” toward Mitigation Flash Flood Disaster) - Erna Desi Faradinah; Dewi Rokhmah; Mury Ririanty (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Flash flood was happened in Kemiri village Panti district Jember Regency on2006.Flash flood disaster caused 76 people died, majority of flash flood victims werechildren. After flash flood, there were some programs about mitigation flash flooddisaster that hold by Non Government Organitation. But those programs didn’t be inlong term, so society can’t understand more about mitigation flash flood disaster. Theaim of this research was to analyze the influence of film playback “Flash Flood Wary”toward mitigation of flash flood disaster for students in 4th and 5th class of MIBustanul Ulum Kemiri village, Panti district. This research used quantitative methodand research design was pre experimental design. Sample of this research were 32students. Statistic was used Paired Sample T-Test. Data analysis showed that therewas not significant influence of film playback “Flash Flood Wary” in increasingknowledge of flash flood disaster mitigation. Significant result was showed ininfluence of film playback “Flash Flood Wary” to increase attitude of flash flooddisaster mitigation with p=0,000. There was significant influence of film playback“Flash Flood Wary” in increasing self-efficacy of flash flood disaster mitigation withp=0,000Keywords: Mitigation Disaster, Film Playback “Flash Flood Wary”, Knowledge,Elementary School